2016
DOI: 10.4238/gmr.15048626
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of drought tolerance with respect to fiber traits in upland cotton

Abstract: Cotton germplasm was analyzed to investigate its potential for developing water stress tolerance in varieties in the future. Four tolerant (NIAB-78, CIM-482, BH-121, and VH-142) and four susceptible (CIM-446, FH-1000, FH-900, and FH-901) lines were identified of 50 accessions based on their seedling root length. A complete set of diallel crosses among eight selected genotypes was subjected to genetic analysis for fiber property traits. Additive and non-additive genetic variance was involved in the inheritance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
1
0
0
Order By: Relevance
“…For fiber fineness additive genetic effects were important which confirms the finding of Khan et al (2017), while finding of Kamaran et al (2018) reflected it as controlled by additive gene effects. For fiber strength, nonadditive genetic components appeared to be predominant this confirms the finding of Kamaran et al (2018), while Nasimi et al (2016) found that additive effects controlled the character. For fiber length non additive genetic components appeared to be predominant this confirms the finding of Kaleem et al (2016), while Coban and Unay (2017) showed that fiber length is controlled by additive gene action.…”
Section: Aterials and Methodssupporting
confidence: 82%
“…For fiber fineness additive genetic effects were important which confirms the finding of Khan et al (2017), while finding of Kamaran et al (2018) reflected it as controlled by additive gene effects. For fiber strength, nonadditive genetic components appeared to be predominant this confirms the finding of Kamaran et al (2018), while Nasimi et al (2016) found that additive effects controlled the character. For fiber length non additive genetic components appeared to be predominant this confirms the finding of Kaleem et al (2016), while Coban and Unay (2017) showed that fiber length is controlled by additive gene action.…”
Section: Aterials and Methodssupporting
confidence: 82%
“…A large genetic and breeding population for drought tolerance was only briefly evaluated in a few studies [23,24,25,26]. However, research on how drought stress effects cotton yield at the crucial seedling stage is lacking.…”
Section: Resultsmentioning
confidence: 99%